Sensorineural Hearing Loss after Magnetic Resonance Imaging. (17th June 2013) - Mollasadeghi, Abolfazl; Mehrparvar, Amir Houshang; Atighechi, Saeid; Davari, Mohammad Hossein; Shokouh, Pedram; Mostaghaci, Mehrdad; Bahaloo, Maryam
Abstract : Magnetic resonance imaging (MRI) devices produce noise, which may affect patient's or operators' hearing. Some cases of hearing impairment after MRI procedure have been reported with different patterns (temporary or permanent, unilateral or bilateral, with or without other symptoms like tinnitus). In this report, a case of bilateral sensorineural hearing loss in an otherwise healthy patient underwent brain MRI was described. The patient's hearing loss was accompanied with tinnitus and was not improved after 3 months of followup.